Avaliação da microestrutura e da resistência à corrosão na soldagem multipasse do aço inoxidável superduplex UNS S32750 pelo processo MIG/MAG. - Batista, Higor Jonas (2012)
Superduplex stainless steels are alloys that have good corrosion and mechanic resistance and, even more, are being used in substitution of austenitic stainless steels. However, welding thermal cycles may deteriorate these properties, affecting ferrite/austenite microstructural ratio and inducing intermetallic phases precipitation, thus requiring an adequate welding parameters selection. This problem might be critical in multipass welding due to repeated thermal cycles. Then, this work aims to study the effect of GMAW parameters on microstructural transformations and corrosion resistance of UNS S32750 superduplex stainless steel multipass welding. Thus, heat input (0,6 kJ/mm, 1,0 and 2,0 kJ/mm), shielding gas composition (98%Ar + 2%CO2 and 60%Ar + 38%He + 2%CO2), current wave shape (continuous and pulsed current) triangular weaving) were selected as the control factors and levels to be evaluated. Welds were performed on “half V” butt joints with 45º bevel angle and thickness of 22 mm. Mixed level fractional factorial technique was selected to the experimental design, resulting in eight butt joints welded. A microstructural characterization was performed on Weld Metal (WM) and Heat Affected Zone (HAZ) by Optical Microscopy (OM) and Scanning Electron Microscopy (SEM). As response characteristics, one evaluated ferrite fraction and austenite mean spacing (both by image analysis), chemical composition of ferrite and austenite phases (Energy Dispersive X-ray Spectroscopy - EDS) and corrosion resistance (by electrochemical potentiodynamic polarization and electrochemical impedance spectroscopy). The results indicated that the heat input was the factor that exerted the greatest influence on the average content of ferrite at the cap of the joints. At root, the waveform and the shielding gas also influenced on this trait. It was observed that the elemental partitioning between ferrite and austenite phases is higher in the HAZ than in the WM, but there is not a tendency of this characteristic as a function of the heat input. The secondary austenite fraction presented a nonlinear relationship at the cap of the joints and the presence was greater when 1,0 kJ/mm heat input was used. Regarding to pitting corrosion resistance, polarization tests showed that the stability of the pits depends on the temperature of the solution, and the nucleation presents a relationship with the regions where there was precipitation of nitrides. Only at the region of the cap that had the highest average levels of ferrite in WM was possible to observe the occurrence of stable pits in this region, in all other cases they occurred in the HAZ. The electrochemical impedance spectroscopy showed a tendency to increase the polarization resistance of the welded joints with increasing the heat input level.